Law Enforcement Against Perpetrators of Desertion by TNI Members in the Military Court Area III-12 Surabaya - Imam Wahyudi; Adies Kadir (Faculty of Law, Merdeka University Surabaya, Indonesia, 2024)
The aim of the research is to determine the implementation of the law enforcement process against deserters at the III-12 Surabaya military court. research methods. Research methods Legal research using normative legal research methods. The results of the implementation by the judge in determining the provisions for the perpetrator in this case are in accordance with the elements of Article 87 paragraph (1) 2nd jo paragraph (2) where the judge has considered both the facts at the trial, the statements of the witnesses and the available evidence, as well as the judge's confidence in handing down a decision which will later have a deterrent effect on the defendant, gives fear to the convict and the Soldiers.